Energy-efficient data security schemes for mobile users in cloud environment / Abdul Nasir Khan - Khan, Abdul Nasir (2014)
Cloud computing is an emerging computing paradigm that offers on-demand, flexible, and elastic IT services for the end-users. The small and medium-sized business organization having limited budget can enjoy the scalable services of the cloud. However, the migration of the organizational data on the cloud raises security and privacy issues that need to be addressed. The problem becomes more sophisticated in mobile cloud computing environment due to resource limitation of mobile devices. To cope with the resource limitation of mobile devices, there are two approaches adopted in the literature while providing security services (a) local execution and (b) remote execution. In local execution approach, the computational complexities of cryptographic algorithms are reduced and the entire security operations are executed using limited computational power of mobile devices. In remote execution approach, the computational intensive security operations are migrated from a resource constraint mobile devices to the resource enrich third-party or cloud for execution. This study investigates the impact of the existing data security schemes on resources utilization of mobile device. A novel energy-efficient data security schemes are proposed to improve the resources utilization on the mobile device by (a) reducing the computational complexity of the cryptographic algorithm and (b) by offloading the computationally intensive operation on the trusted entity or cloud. The proposed schemes are compared with the existing schemes on the basis of energy consumption, CPU utilization, memory utilization, encryption time, decryption time, and turnaround time on mobile device. The experimental results indicate that the proposed schemes show significant improvement in results as compared to the existing schemes. Keywords: Cloud Computing, Mobile Cloud Computing, Security, Privacy